A collaborative web-based platform for the prescription of Custom-Made Insoles. (August 2017) - Mandolini, Marco; Brunzini, Agnese; Germani, Michele
Highlights: Innovative workflow to design and prescribe Custom-Made Insoles (CMIs). Web-based platform integrating devices used during the CMIs development process. Platform integrating the stakeholders involved during the CMIs development process. Innovative knowledge-based system for prescribing Custom-Made Insoles. Abstract: Many foot pathologies are prevented or treated with Custom Made Insoles (CMIs). Although a strong computerization has characterized the shoe development process during the last decade, the CMI sector still lacks a software platform integrating the design and diagnosis tools used by the stakeholders of this area. Moreover, the prescription of CMIs is only based on the experience of skilled podiatrists rather than on a common and shared knowledge (e.g. guidelines, best practices, rules, etc.). This paper presents a multi-users and knowledge-based platform, called Smart Prescription Platform ( SPP ), covering the whole CMI development phases, from foot diagnosis to the production, involving clinicians, patients, manufacturers and controllers. The web-based platform is fully integrated with the technologies available in the orthopaedic sector, which are 3D/4D scanners, baropodometric platforms, footwear virtual catalogues, plantar pressure simulators, Augmented Reality devices and 3D CAD systems. The use of standard file formats (e.g. .stl, .bmp, .xml ) allows an electronic dataflow among the tools. The main module of the platform, called Prescription System (PS), is used for prescribing custom-made insoles for patients with different health conditions, satisfying the needs of all actors and optimizing the data exchange. PS is a knowledge-based prescription system integrating the best practices related to the prescription of CMIs. The PS output is a XML file representing the electronic order, used to exchange data with the other tools of the SPP . The proposed platform has been tested with a twofold aim: to validate the usability of the Prescription System and the inter-operability of the platform tools. The positive results gathered during the validation, led the experts to start using the web platform for their daily work.